2015
DOI: 10.1371/journal.pone.0131037
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Bioluminescent Nitroreductase Probe for Preclinical Imaging

Abstract: Bacterial nitroreductases (NTRs) have been widely utilized in the development of novel antibiotics, degradation of pollutants, and gene-directed enzyme prodrug therapy (GDEPT) of cancer that reached clinical trials. In case of GDEPT, since NTR is not naturally present in mammalian cells, the prodrug is activated selectively in NTR-transformed cancer cells, allowing high efficiency treatment of tumors. Currently, no bioluminescent probes exist for sensitive, non-invasive imaging of NTR expression. We therefore … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
39
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 55 publications
0
39
0
Order By: Relevance
“…Work from our laboratory and others has demonstrated the utility of caged luciferins in vivo (28)(29)(30) for measuring transient small molecules (31)(32)(33)(34), enzyme and transporter activities (34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46), protein-protein and cell-cell interactions (42,47,48), and copper (49). Indeed, previous work from our laboratory utilized a Cu-dependent oxidation reaction to uncage luciferin for in vivo copper imaging (50), a first demonstration of a general activitybased sensing (ABS) strategy which we envisioned expanding to other essential metals in biology by changing the reaction trigger.…”
mentioning
confidence: 99%
“…Work from our laboratory and others has demonstrated the utility of caged luciferins in vivo (28)(29)(30) for measuring transient small molecules (31)(32)(33)(34), enzyme and transporter activities (34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46), protein-protein and cell-cell interactions (42,47,48), and copper (49). Indeed, previous work from our laboratory utilized a Cu-dependent oxidation reaction to uncage luciferin for in vivo copper imaging (50), a first demonstration of a general activitybased sensing (ABS) strategy which we envisioned expanding to other essential metals in biology by changing the reaction trigger.…”
mentioning
confidence: 99%
“…The conversion of fluorogenic compounds during cultivation answers if bacteria are viable under the condition of interest [3,4,10]. The role of enzymes in virulence and bacterial survival is of high interest for basic research as well as future oriented therapeutic strategies [7,9,11].…”
Section: Discussionmentioning
confidence: 99%
“…Novel applications with those chemical compounds for bacterial detection [4][5][6], metabolic characterization [2,7,8], drug development [9], preclinical studies [10], and screening for antibiotic resistance [11] are reported.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations